ANALISIS SISTEM DAN PROSEDUR AKUNTANSI PENGELUARAN KAS PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KUTAI KARTANEGARA - Camelia Verahastuti3, Holiyah1, Eddy Soegiarto2 (EKONOMIA, 2018)
HOLIYAH, The study of system analysis and accounting procedures cash Procedures Accounting   disbursements at Regional Finance and Asset Management Agency (BPKAD) Accounting Cash             Kutai Kartanegara, under the guidance of Mr. Eddy Soegiarto as lecturer I Disbursements                   and Mr.Camelia Verahastuti as a supervising lecturer II. Accounting Systems and procedures at Regional Finance and Asset Management Agency (BPKAD) Kutai Kartanegara each system and procedure must be performed in accordance with the applicable rules so that it can be the basis decision making in government. The purpose of this research is to know cash accounting system and procedure at Regional Finance and Asset Management Agency (BPKAD) Kutai Kartanegara based on the Minister of Home Affairs Regulation Number 13 of 2006 about local financial management guidelines. Research method in this research is analyze system and procedure accounting for cash disbursements at Regional Finance and Asset Management  (BPKAD) Kutai kartanegara  in  2017 by using analytical tool that is comparative method, So that cash disbursements accounting system and procedure at Regional Finance and Asset Management Agency (BPKAD) Kutai Kartanegara compared with Regulation of the Minister of Home Affairs Number 13 of 2006 concerning Guidelines on Regional Financial Management. The result of research using formula of calculation of champion method in system and procedure accounting cash disbursements is on Regional Finance and Asset Management (BPKAD) Kutai Kartanegara in 2017, it can be concluded that the application of accounting system and cash disbursements procedures at Regional Finance and Asset Management Agency (BPKAD) Kutai Kartanegara it is in accordance with the Minister of Home Affairs Regulation Number 13 of 2006 96 % and hypothesis testing can be concluded that the hypothesis is rejected. Based on the result of the research, it can be concluded that the Regional Finance And Asset Management Agency (BPKAD) Kutai Kartanegara already covers in accordance with the Minister of Home Affairs Regulation No. 13 of 2006. We recommend the Regional Financial and Asset Management Agency (BPKAD) improve and maintain systems and procedures for cash out of inventory and is expected to continue to follow applicable regulations